Making Sense of Populist Nationalism. Issue 2 (4th March 2021) - Gamble, Andrew
ABSTRACT: One of the blind spots of political economy in its response to the financial crisis and its aftermath is the tendency to attribute contingency and rationality to long-run economic developments, but to attribute contingency and irrationality to political trends and developments. This reflects the continuing legacy of economism in the political economy tradition. Critical political economists anticipated the financial crisis but not the political responses to the crisis, including the resilience of neo-liberalism and the upsurge of populism and nationalism in many western democracies. The temptation to dismiss the economic policies of these new nationalists as economically irrational and superficial because they interfere with the logic and superior rationality of global capital is reminiscent of some of the political-economic analyses of the neo-liberal turn in the 1970s and 1980s. A critical political economy seeking to make sense of the variety of populist nationalist insurgencies needs to overcome the binary distinction between cultural and economic logics by accepting that there are different rationalities rather than a single homogenous economic rationality on one side and political and ideological irrationalities on the other.